Who would believe a prisoner? : Indiana women's carceral institutions, 1848-1920 - Jones, Michelle Daniel; Nelson, Elizabeth (Historian) (The New Press, 2023)
"A groundbreaking collective work of history by a group of incarcerated scholars that resurrects the lost truth about the first women's prison"--